Digital equity in education: A Multilevel examination of differences in and relationships between computer access, computer use and state-level technology policies. - Becker, Jonathan D. (Education Policy Analysis Archives, 2007)
Using data from the National Assessment of Educational Progress (NAEP) state assessment and a survey of state-level technology policies, this study examined digital equity in education as a multilevel organizational phenomenon with data from 70,382 students in 3,479 schools and 40 states. Students in rural schools or schools with higher percentages of African American students were likely to have less access to computers. With respect to computer use, girls and students eligible for free or reduced-price lunch were more likely to use computers more frequently when computers are available in the classroom. With respect to relationships between computer access and computer use, having computers available in a lab increases the likelihood of higher levels of computer use. The results suggested that no more than 5% of the variance in computer access can be attributed to state factors, and less than 1% of the variance in computer use was between states. The findings suggested that where student technology standards are integrated into subject-area standards, computer use was likely lower than in other states. In states where pre-service teachers must meet technology-related requirements to receive their teaching credential and states where funds earmarked for technology are distributed as competitive grants, computer use was likely to be higher.